TINGKAT STRES DENGAN STRATEGI KOPING PADA SISWA FULL DAY SCHOOL - Imamah, Ida Nur; Mulyaningsih, Mulyaningsih; Asiska, Asiska (Jurnal Ilmiah Kesehatan, 2021)
Purpose: To determine the relationship between stress levels and coping strategies of full day school students at Al Abidin Islamic Middle School in Surakarta. Method: Quantitative research is correlational analytic with Cross Sectional design. Sampling using the Stratified Random Sampling technique with a total sample of 79 respondents, and the research instrument using a questionnaire. Bivariate analysis using Chi Square test. Results: That the majority of full day school students have high stress levels of 60 respondents (75.9%), and use maladaptive coping strategies of 53 respondents (67.1%). The chi square test results obtained ρ value 0.068 greater than ɑ of 0.05, so there no relationship between variables. Conclusion: There is no correlation between stress level and coping strategies of full day school students at Al Abidin Islamic Middle School in Surakarta.